From green fingers and green ring to green mitten: Helsinki’s polycentric urbanisation and its impact on green structure - leBrasseur, Richard (European Spatial Research and Policy, 2024)
Urbanisation changes the landscape and fragments spatial structures including greenspaces across much of the world and Europe. The resultant impacts and morphological characteristics are understudied within peri-urban regions of cities. This study analysed the spatial qualities and relationship among peri-urban greenspaces, green structure, and urban form within the Greater Helsinki Region of Finland. Results illustrate how the existing ‘Green Fingers’ have impacted urban development patterns. Though the region includes many fragmented greenspaces, an overall interconnected and coherent intermixed green structure remains. This spatial component faces continued threats; managing the growth of peri-urban regions is critical to maintaining a green structure’s functional and morphological benefits.